Study of Cutaneous Manifestations in End Stage Kidney Disease Undergoing Hemodialysis - Abhishek Maskey; Ajay Kumar; Roshan Shrestha (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: The prevalence of cutaneous manifestations in hemodialysis patients is increasing.